Serum Response Factor Regulates Expression of PTEN through a Micro-RNA Network in Vascular Smooth Muscle Cells - Horita, Henrick N (2011)
OBJECTIVE: Serum response factor (SRF) is a critical transcription factor in smooth muscle cells (SMC) controlling differentiation and proliferation. Our previous work demonstrated that depleting SRF in cultured SMC decreased expression of SMC markers, but increased proliferation and inflammatory mediators. A similar phenotype has been observed in SMC silenced for PTEN, suggesting that SRF and PTEN may lie on a common pathway. Our goal was to determine the effect of SRF depletion on PTEN levels, and define mechanisms mediating this effect. METHODS AND RESULTS: In SRF-silenced SMC, PTEN protein, but not mRNA levels were decreased, suggesting post-transcriptional regulation. Re-introduction of PTEN into SRF-depleted SMC reversed increases in proliferation and cytokine/chemokine production, but had no effect on SMC marker expression. SRF-depleted cells showed decreased levels of miR-143, and increased miR-21, which was sufficient to suppress PTEN. Increased miR-21 expression was dependent on induction of FRA-1, which is a direct target of miR-143. Introducing miR-143 into SRF-depleted SMC reduced FRA-1 expression and miR-21 levels and restored PTEN expression. CONCLUSIONS: SRF regulates PTEN expression in SMC through a miR network involving miR-143, targeting FRA-1, which regulates miR-21. Cross talk between SRF and PTEN likely represents a critical axis in phenotypic remodeling of SMC.